Development of a microcontroller-based, photovoltaic maximum power point tracking control system. - Koutroulis, E. (IEEE Transactions on power electronics)
Maximum power point tracking (MPPT) is used in photovoltaic (PV) systems to maximize the photovoltaic array output power, irrespective of the temperature and irradiation conditions and of the load electrical characteristics. A new MPPT system has been developed, consisting of a buck-type DC/DC converter, which is controlled by a microcontroller-based unit. The main difference between the method used in the proposed MPPT system and other techniques used in the past is that the PV array output power is used to directly control the DC/DC converter, thus reducing the complexity of the system. The resulting system has high-efficiency, lower-cost and can be easily modified to handle more energy sources (e.g., wind-generators). The experimental results show that the use of the proposed MPPT control increases the PV output power by as much as 15% compared to the case where the DC/DC converter duty cycle is set such that the PV array produces the maximum power at 1 kW/m2 and 25°C